2016
DOI: 10.1016/j.molonc.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy of combined HDAC and PARP targeting in glioblastoma

Abstract: IntroductionGlioblastoma (GBM) is among the deadliest of solid cancers with striking genomic instability and therapeutic resistance. Despite extensive efforts, the prognosis of patients suffering from this aggressive disease remains poor with median survival of approximately 15 months (Chen et al., 2012;Huse et al., 2011;Stupp et al., 2005;Tanaka et al., 2013). The standard of care represents maximal-safe surgical resection followed by chemo-radiation (Stupp et al., 2005). Based on successful pre-clinical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 44 publications
2
48
1
Order By: Relevance
“…This was concordant with our previous work showing that induction of ROS and oxidative DNA lesions renders GBM cells dependent on functional PARP (ref. 38). …”
Section: Resultsmentioning
confidence: 99%
“…This was concordant with our previous work showing that induction of ROS and oxidative DNA lesions renders GBM cells dependent on functional PARP (ref. 38). …”
Section: Resultsmentioning
confidence: 99%
“…Singh and colleagues reported that an FDA-approved HDAC inhibitor vorinostat in combination with tranylcypromine, can reduce GBM stem cell viability in a GBM xenograft model and lead to changes in apoptosis-regulatory genes such as TP53 and TP73 [ 141 ]. HDAC inhibitor SAHA shows strong effects in destabilizing mut-p53 by dissociating HDAC6 from functional interaction with Hsp90 and thereby inhibits GBM growth and resistance to chemotherapy [ 142 , 143 , 144 , 145 , 146 ]. However, SAHA was recently found to also down regulate wt-p53 [ 147 ], suggesting that it should be applied only to homozygous mut-p53 tumors.…”
Section: P53-targeted Therapiesmentioning
confidence: 99%
“…Olaparib, is a poly (adenosine diphosphate [ADP]-ribose) polymerase 1 (PARP1) inhibitor, capable of suppressing activities of PARP1 in single-strand break (SSB) repair [27]. PARP inhibitors have been shown in several studies to control glioblastoma growth in combination with different agents [28,29] and are currently being evaluated in six different clinical trials. Importantly, the catalytic subunit of ribonucleotide reductase M2 (RRM2) which we determined to be regulated by Msi1, protects GBM cells from replication stress, DNA damage and apoptosis.…”
Section: Luteolin Sensitizes Glioblastoma Cells To Radiation and Parpmentioning
confidence: 99%